A Review of the Use of UHPFRC in Bridge Rehabilitation and New Construction in Switzerland - Bertola, Numa; Schiltz, Philippe; Denarié, Emmanuel; Brühwiler, Eugen (Frontiers in Built Environment, 2021)
Ultra-High-Performance Fibre Reinforced Cementitious Composite (UHPFRC) provides solutions to enhance existing structures and design innovative new structures. Structural UHPFRC offers 3–5 times higher compressive and tensile strengths than ordinary concrete. Due to its strain-hardening behavior and dense matrix, structures made of UHPFRC remain crack-free and waterproof, guaranteeing durability. UHPFRC has been used particularly in Switzerland with more than 280 applications since 2003. A review of UHPFRC applications in the country is proposed in this paper. Ten bridge case studies are presented, including five strengthening of existing structures and five new designs. These structures were chosen to assess the multiple benefits that UHPFRC provides compared to traditional reinforced-concrete structures. Besides structural efficiency, several construction criteria are considered, such as construction costs, material durability, environmental impacts, and construction time. Structural rehabilitation made with UHPFRC leads to cost-effective interventions, and this material also helps to preserve heritage structures. Due to its specific mechanical properties, UHPFRC enables new structures with distinctive aesthetic designs with reduced construction time. The crucial contribution of research to the first case studies is also highlighted. This link between Swiss universities and the construction industry has quickly transitioned UHPFRC Technology from academic studies to real-world applications. Nowadays, the UHPFRC Technology is maturing and applications are common in the country.